The relationship between autophagy and apoptosis during pseudorabies virus infection - Sun, Mingxia; Hou, Linlin; Song, Huan; Lyu, Chuang; Tang, Yan-dong; Qin, Lei; Liu, Yonggang; Wang, Shujie; Meng, Fandan; Cai, Xuehui (Frontiers in Veterinary Science, 2022)
Both autophagy and apoptosis are mechanisms that maintain homeostasis in cells and that play essential roles in viral infections. Previous studies have demonstrated that autophagy and apoptosis pathways occurred with complex relationships in virus-infected cells. However, the regulation between these two processes in Pseudorabies virus (PRV) infection remains unclear. In the present study, we demonstrated that activated autophagy was induced at the early stage of PRV infection and that apoptosis was induced at the late stage of infection. Autophagy induction inhibited apoptosis and decreased viral replication, and autophagy inhibition promoted apoptosis and increased viral replication. We also found that viral infection resulted in an increase in the production of reactive oxygen species (ROS) and activation of apoptosis in autophagy-impaired cells, suggesting that ROS may participate the crosstalk between autophagy and apoptosis in PRV-infected cells. Our studies provide possible molecular mechanisms for the crosstalk between apoptosis and autophagy induced by PRV infection in porcine cells, which suggests that these two cell death processes should be considered as the same continuum rather than as completely separate processes.